Studying service-learning : innovations in education research methodology - Billig, Shelley; Waterman, Alan S. (L. Erlbaum Associates, 2003)
This volume represents a breakthrough discussion of the research issues surrounding innovative pedagogies. Using service-learning as its focus, it explores ways in which researchers and evaluators can study a teaching and learning approach that has multip.